Efeitos do exercício físico na expressão do LTB4R1 em camundongos swiss obesos - Callegari, Irineu Otavio Marchiori [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The global obesity epidemic brings with it increased levels of subclinical and chronic inflammation, in addition to increased insulin resistance (IR) in adipose tissue, skeletal muscle and liver, which certainly contributes to the development of chronic diseases. Recently, the role of leukotriene B4 (LTB4) was discovered, a lipid molecule compatible with the polarization of macrophages in the M1 sense and chemotaxis of adaptive immune cells when coupled to its receptor (LTB4R1). The increase in the expression of LTB4 occurs in the presence of the IR established by the high fat diet (DH). Thus, we aimed to attenuate the inflammatory state of obese Swiss mice treated with HD through physical exercise, considered a non-pharmacological tool to regulate glycemic metabolism and inflammation. The animals were divided into groups: control animals (CTL), obese animals fed a high fat diet (HD), chronically exercised animals (4 weeks, 5 times a week) and fed a high fat diet (DH+EC), and acutely exercised animals and fed a high fat diet (DH+EA). After 12 weeks, intraperitoneal glucose (GTT) and insulin (ITT) tolerance tests were performed, which indicated increased fasting glucose, glucose intolerance, and reduced insulin signaling together with significant weight gain in the fed groups. in DH. Four weeks of moderate-intensity aerobic physical exercise was not enough to significantly reduce the animals' body weight, but there was a significant reduction in glucose intolerance and an improvement in insulin sensitivity in the DH+EA and DH+EC groups in the face of immunoblotting analyses, as well as an improvement in serine phosphorylation of IR and AKT. There was an increase in LTB4R1 mRNA in skeletal muscle, verified by Real Time RT-PCR. Chronic exercise partially reduced LTB4R1 and TNF-α levels in skeletal muscle and adipose tissue, followed by a non-significant increase in IL-4 expression in skeletal muscle, liver and adipose tissue. Physical exercise showed a tendency to improve LTB4 expression in skeletal muscle, but it was considered insufficient to reverse the levels of inflammation achieved by a high-fat diet. Keywords: obesity, inflammation, insulin resistance, physical activity, immune system, health.

A epidemia global de obesidade traz consigo a aumento dos níveis de inflamação subclínica e crônica, além do aumento da resistência à insulina (RI) no tecido adiposo, músculo-esquelético e fígado, e que certamente contribui com o desenvolvimento de doenças crônicas. Recentemente, foi descoberto o papel do leucotrieno B4 (LTB4), molécula lipídica compatível a polarização de macrófagos em sentido M1 e quimiotaxia de células da imunidade adaptativa quando acoplada ao seu receptor (LTB4R1). O aumento da expressão de LTB4 ocorre na presença da RI instaurada pela dieta hiperlipídica (DH). Dessa forma, objetivamos atenuar o estado inflamatório de camundongos swiss obesos tratados com DH por meio da pratica do exercício físico, considerado ferramenta não-farmacológica para regular o metabolismo glicêmico e a inflamação. Os animais foram divididos em grupos: animais controle (CTL), animais obesos alimentados com dieta hiperlipídica (DH), animais exercitados cronicamente (4 semanas, 5 vezes na semana) e alimentados com dieta hiperlipídica (DH+EC), e animais exercitados agudamente e alimentados com dieta hiperlipídica (DH+EA). Após 12 semanas, foram realizados testes de tolerância intraperitoneal à glicose (GTT) e à insulina (ITT), que indicou aumento da glicemia de jejum, intolerância à glicose e redução da via de sinalização à insulina em conjunto com o ganho de peso significativo dos grupos alimentados em DH. Quatro semanas de exercício físico aeróbio de moderada intensidade não foram suficientes reduzir significativamente o peso corporal dos animais, mas houve redução significativa da intolerância à glicose e melhora da sensibilidade à insulina nos grupos DH+EA e DH+EC diante das análises de imunoblotting, assim como melhora da fosforilação em serina de IR e AKT. Houve aumento do RNAm de LTB4R1 no músculo-esquelético, verificado por meio da RT-PCR Real Time. O exercício crônico reduziu parcialmente os níveis de LTB4R1 e TNF-α no músculo-esquelético e tecido adiposo, seguido de aumento não significativo da expressão de IL-4 no músculo-esquelético, fígado e tecido adiposo. O exercício físico mostrou uma tendência de melhora na expressão do LTB4 no músculo-esquelético, porém foi considerado insuficiente para reverter os níveis de inflamação alcançados pela dieta rica em gordura. Palavras-chave: obesidade, inflamação, resistência à insulina, atividade física, sistema imune, saúde.
Effects of physical exercise on LTB4R1 expression in obese swiss mice
Keywords: Obesidade; Inflamação; Atividade física; Sistema imune; Resistência à insulina; Saúde; Obesity; Inflammation; Physical activity; Immune system; Insulin resistance; Health